Comparative study of the C3d receptor and 58-kilodalton fibrinogen-binding mannoproteins of Candida albicans. - López-Ribot, J L (1995)
Using polyclonal antibodies (PAbs) raised against the Candida albicans C3d receptor (CR2; PAb anti-CR2) and the 58-kDa fibrinogen-binding mannoprotein (mp58; PAb anti-mp58) as well as ligand interactions, we have studied the relationship between these two receptors. In an indirect immunofluorescence assay with germ tubes, greater intensity was observed on the mother blastoconidium when PAb anti-CR2 was used, whereas greater intensity was localized to the hyphal extension when PAb anti-mp58 or binding of soluble fibrinogen was used. No competition or change in the fluorescence pattern was observed in dual-labeling experiments with PAb anti-CR2 and either fibrinogen or PAb anti-mp58. Binding competition also was not observed in an enzyme-linked immunosorbent assay using the components present in a beta-mercaptoethanol extract from the cell wall of germ tubes. In immunoblots, PAb anti-CR2 recognized three different discrete bands with apparent molecular masses of 21, 40, and 66 kDa in the beta-mercaptoethanol extracts from the cell wall, whereas a different, single, broader band with an apparent molecular mass of 58 kDa was detected with PAb anti-mp58. However, when nondenaturing conditions were used to separate the materials present in the cell wall extracts, no reactivity could be detected on Western blots (immunoblots) with PAb anti-mp58. When PAb anti-CR2 was used for analysis, a single band migrating in the area corresponding to approximately 40 kDa was detected. These observations suggest a higher molecular weight for mp58 and one or more of the components detected with PAb anti-CR2 in their native state.